The Protective Effects and Mechanism of Resveratrol-loaded Nanoparticles on HK-2 Cells Suffering from Hypoxia-reoxygenayion - Li, Hailun; Hu, Yu; Xu, Yong; Zhong, Lili; Lin, Yongtao; Da, Xi; Yu, Weinan; Zheng, Donghui (Current Signal Transduction Therapy, 2015)
Kidney ischemia-reperfusion injury is a serious illnesses which could threaten to human health. However, there is lack of effective therapy for the disease. Recently, resveratrol (Res) has been reported as a potential antioxidant in treatment of ischemia/reperfusion injury through attenuating oxidative stress and apoptosis. Because of its insolubility and short half-time, the application of Res is limited. Latest evidence reveals the possibility of developing nanoparticle-based delivery systems with improved solubility, stability and cytotoxicity of lipophilic drug. Here, we use Res-loaded nanoparticles (Res-NPs) to evaluate the protective effect of Res-NPs on human renal proximal tubular epithelial (HK-2 cells) suffering hypoxia-reoxygenayion in vitro. The hypothesis is raised that Res-NPs could demonstrate enhanced renal protection compared to an equivalent dose of free Res at lower concentration. Res-NP can significantly improve the survival rate of HK-2 cells and reduce the number of apoptosis cell. It also can reduce the activity of reactive oxygen species (ROS), decrease the level of Caspse-3 & Bax and increase the level of Bcl-2. Res-NP can inhibit hypoxia reoxygenation of HK-2 cells apoptosis better than Res, which mechanism is related to its antioxidation. Res-NPs could be a potential treatment needing intensive research for ischemia/reperfusion.
Keywords: resveratrol